Circular thinking: the Yamanote line on film. Issue 2 (3rd April 2018) - Coates, Jennifer
Abstract: Cinema and the railway are intimately connected; the train window view mirrors the kinetic representation of everyday life on film. While pre-war filmmakers used the train to symbolize Japan's rapid modernization, after 1945 train imagery began to take on new meanings as the railway became associated with horrors perpetrated during the Asia Pacific war. The Yamanote line in contemporary film symbolizes this confluence of modernity, technology, possibility and historical trauma. Its circular nature constitutes a blockage in the context of the historical design of Japanese cities to favour flow, and so the Yamanote line often functions as a static holding space, a space in which protagonists contemplate and work through obstacles or trauma. From the art-house to the blockbuster, recent films have employed the line as a metaphor for blockage, transformation and the eventual overcoming of obstacles. In Hou Hsiao-Hsien's Café Lumiere (2003), a young woman considers her unplanned pregnancy on the Yamanote line, while the Korean–Japanese production 26 Years Diary (2007) uses the space to depict a young Korean student coming to terms with Korean–Japanese history. The Yamanote line is an explicitly international space in these films, in which human relationships allegorize Japan's relation to its ex-colonies. Material cultural exchange is facilitated by the variety of international spaces the circular track passes through. The enclosed line is therefore a metaphor for Japan's engagement with its neighbours within its own national sphere, as well as a space in which protagonists consider solutions to problems at once personal, cultural, political and national.